Social Support and Resilience among People Living with HIV/AIDS in Yogyakarta, Indonesia - Ulfa, Nabilla Dwi; Kusumaningrum, Fitri Ayu (Unisia, 2024)
This study explores the relationship between social support and resilience in individuals living with HIV/AIDS. Resilience, defined as the ability to adapt and recover from adversity, is critical for psychological well-being, especially in the face of stigma and discrimination commonly experienced by people with HIV/AIDS. The research aims to determine whether social support significantly contributes to enhancing resilience among this population. The study employed a quantitative approach, involving 64 individuals diagnosed with HIV/AIDS in Yogyakarta, Indonesia. Data were collected using the Multidimensional Scale of Perceived Social Support and the Connor-Davidson Resilience Scale. Statistical analyses, including Pearson’s Product-Moment Correlation and Spearman’s Rho, were conducted to test the hypothesis that higher social support is positively correlated with increased resilience. The findings reveal a significant positive correlation between social support and resilience, with a correlation coefficient of 0.511 and a p-value of 0.000. Resilience levels among participants were generally low, with 81.2% categorized as "very low." Social support levels were similarly low, with 51.56% of participants in the "very low" category. Family, friends, and significant others were identified as key sources of social support, contributing 18.9%, 23.8%, and 27.2% to resilience, respectively. The study also found that social support was particularly impactful on aspects of resilience such as persistence and hardiness. The results underscore the importance of social support in fostering resilience among people living with HIV/AIDS. Enhanced social support networks contribute significantly to their psychological adaptation and ability to cope with adversity. Conversely, a lack of support exacerbates vulnerability and diminishes resilience.